Socio-demographic differences in Colombian children's muscular fitness: Does scaling for differences in body size present a challenge to conventional thinking? (2018)
Objectives: In low- to middle-income countries, children from less-deprived areas (from families of higher socio-economic status [SES]) have superior muscular fitness than those from low-SES groups. They are also taller and heavier, factors associated with muscular fitness. The purpose of this study was to identify any socio-demographic differences in Colombian children's muscular fitness and examine how these conclusions can be modified by scaling for differences in body size. Methods: A total of 38,098 youths (46% girls), ninth grade students (aged 14–15 years), participated in a study of cross-sectional design. We recorded SES and family incomes, stature, and mass. Standing broad jump and handgrip strength were used to assess muscular fitness. A multiplicative allometric model was adopted to adjust for body-size differences. Results: Children from the mid- to high-SES groups jumped significantly higher than children from the lowest SES group, although no SES group difference in grip strength was observed. After adjusting for body size, children from higher SES and with higher family incomes had significantly lower handgrip strength, and their superior jump height performances remained but were greatly reduced. Only children from the highest SES now jumped significantly higher that the lowest SES group. Conclusions: The superior jump performance and no difference in handgrip strength of Colombian children from higher SES may simply reflect their superior physiques. When body size is accounted for, these differences are reduced or even reversed, suggesting that children from higher SES groups should not be complacent regarding their apparent superior muscular fitness. © 2018 Wiley Periodicals, Inc.